Expression of Vascular Endothelial Growth Factor and Anti-Proliferative Activity of Flaxseed Oil Alone and In Combination with Mefenamic Acid in Cell Lines - Alzubaidy, Noor; Sahib , Hayder (Iraqi Journal of Pharmaceutical Sciences, 2024)
The flaxseed oil contains alpha-linolenic acid, lignans and flavonoids. It possesses anti-inflammatory, antioxidant, and tumor-suppressive effects. The purpose of this research was to explore the anti-proliferative effect of flaxseed oil alone and flaxseed oil in combination with mefenamic acid on human umbilical vein endothelial cells and Kaposi sarcoma cells and to identify the vascular endothelial growth factor gene expression. The anti-proliferative effects of flaxseed oil alone and in combination with mefenamic acid were investigated in vitro by the 3-(4, 5-Dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay. The effects of flaxseed oil alone and its combination with mefenamic acid were tested on the expression of vascular endothelial growth factor genes using real-time polymerase chain reaction. The results showed that the IC50 of flaxseed oil for human umbilical vein endothelial cells was 29.72 µg/ml and for Kaposi sarcoma cells was 16.48 µg/ml; moreover, the IC50 for flaxseed oil in combination with mefenamic acid for human umbilical vein endothelial cells was 252 µg/ml and for Kaposi sarcoma cells was 147.6 µg/ml. These outcomes revealed that flaxseed oil alone and its combination with mefenamic acid possess anti-angiogenic activity in a concentration-dependent manner which supported by significant decline in vascular endothelial growth factor expression.